Nursing students' stressors and anxiety in their first clinical practice - Ana Isabel Cobo Cuenca; Raquel Carbonell Gómez de Zamora; Concepción Rodríguez Aguilera; Inmaculada Vivo Ortega; Rosa Mª Castellanos Rainero; Asunción Sánchez Donaire (Fundación para el Desarrollo de la Enfermería, 2010)
Nursery practices are crucial for the subsequent professional development of the nurse, but because of her contact with suffering, death and in general the human aspects of health care, mean a stressful moment for nursing students.Objectives: know the levels of anxiety and condition, as well to determine the stressors that have influence in such anxiety in the students of Nursing Schools of the University of Castilla la ManchaMethodology: A observational, longitudinal and prospective study. The Stai-R and Stai-E questionnaires will be used to know the anxiety trait and state and the Kezkak questionnaire, validated by Zupiria, will be used to know the most frequent stressors that appear in the population subject of this survey.The population is limited to the students registered for the Introductory Practicum subject, that mean the first practices and therefore the student's first contact with the reality of the nursery care.The analysis of information will be realized by statistical package SPSS V15.0.